Para além da formação neoliberal de capital humano: Nussbaum e a formação enquanto cultivo da humanidade - Scolari, Adriel Paulo (2022)
The present thesis defends the idea of training as the cultivation of humanity as a counterpoint to the neoliberal model formation of human capital. The problem that moved the research presented here is summarized by the following question: How was education, as a human formation, has been usurped by the conception of neoliberal formation of human capital and what is the reach of Nussbaum's theory of the cultivation humanity to delineate a renewed model of human formation? To answer it, we used bibliographical research as a method and the hermeneutic posture as a way of understanding the texts, delimiting them through reading keys that emerged during the investigation. Based on a diagnosis of the time made with the help of Martha Nussbaum, Pierre Dardot and Christian Laval, we arrive at the key concepts that may be responsible for these changes, namely, Neoliberalism and the Theory of Human Capital. We took the work Birth of Biopolitics, by Michel Foucault, to understand the constituent aspects of neoliberalism, as well as the texts of the founding economists of the, Theodore Schultz and Gary Becker, to find explanations about this neoliberal formative model. Neoliberalism has become a rationality that stimulates generalized competition between individuals. This competitive logic runs through all spheres of daily life, making contemporary life unbearable. The Theory of Human Capital, on the other hand, with the idea of investing in the subject for the economic development of nations, has become a tool of neoliberalism to penetrate the core of the constitution of subjectivities through education. Neoliberal rationality uses a renewed version of the Theory of Human Capital as a tool to appropriate the soul of subjects. This formative model originated an anti-political and individualist subject who is not concerned with what is public and collective. As an alternative to such a model, we present a proposal for a formation while cultivating humanity, based on the works Cultivation Humanity and Not for profit, in which Martha Nussbaum outlines a “Socratic pedagogy”, the development of a universal citizenship and the capacity for a narrative imagination. We conclude that a formation guided by these aspects can be a powerful strategy of resistance to the shrinking of subjectivity of contemporary subjects. This formation needs, according to the results of this research, to be supported by a State that guarantees investments, by a school that revives its meaning and by professors who are researchers and valued in their profession. Nussbaum's conception of cultivating humanity can drive important elements towards training that develops the broader capabilities of human beings, stimulating a culture of developing subjectivities that are denser than those provided by neoliberal formation of human capital.